The role of fringing vegetation in supporting avian access to arid zone waterholes. (2nd January 2022) - Votto, Simon E.; Schlesinger, Christine; Dyer, Fiona; Caron, Valerie; Davis, Jenny
ABSTRACT: Access to drinking water is essential for many avian species in arid landscapes, especially in hot and dry periods when metabolic requirements for water increase. The role of fringing vegetation in facilitating surface water access by arid zone bird communities was investigated over a 14-month period during which water demand increased. Bird visitation to six long-lasting waterholes in the MacDonnell Ranges Bioregion in central Australia was recorded over two summers and one winter using camera traps. Species were assigned to functional classes based on their size and preferred foraging substrate. Generalised linear mixed models were used to test relationships between fringing vegetation variables and the independent trapping events for each functional class. Fringing vegetation was critical for small and intermediate-sized canopy foragers to access waterhole sites. Their activity declined to almost zero in areas where the nearest tree or shrub cover was greater than 10 m. The strength of this relationship was consistent as weather conditions became drier and hotter. However, activity of small and intermediate-sized canopy foragers was negatively related to the percent canopy cover of the nearest tree or shrub, potentially because sparse vegetative cover offers greater visibility when approaching the water's edge. In contrast, ground forager and raptor activity at waterhole sites was unrelated to surrounding vegetation, and these groups frequently accessed water from open areas. Under future warming scenarios, small and intermediate canopy foragers may be vulnerable to predation if they are forced to access water at sites away from nearby fringing vegetation.